2016
DOI: 10.1073/pnas.1523471113
|View full text |Cite
|
Sign up to set email alerts
|

Inability to suppress salient distractors predicts low visual working memory capacity

Abstract: According to contemporary accounts of visual working memory (vWM), the ability to efficiently filter relevant from irrelevant information contributes to an individual's overall vWM capacity. Although there is mounting evidence for this hypothesis, very little is known about the precise filtering mechanism responsible for controlling access to vWM and for differentiating low-and high-capacity individuals. Theoretically, the inefficient filtering observed in lowcapacity individuals might be specifically linked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
164
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(183 citation statements)
references
References 62 publications
(75 reference statements)
18
164
0
1
Order By: Relevance
“…This revealed no evidence for a selective relationship between the effect of distractor load on target amplitude or distractor amplitudes (all p ’s < 0.25), suggesting that individual differences in how distractor load affected performance did not selectively reflect individual differences in distractor suppression or target enhancement 13 . Instead, individual differences in the effect of distractor load on the relative distribution of attention to target versus distractor locations predicted the effect of distractors on individual performance.…”
Section: Resultsmentioning
confidence: 89%
“…This revealed no evidence for a selective relationship between the effect of distractor load on target amplitude or distractor amplitudes (all p ’s < 0.25), suggesting that individual differences in how distractor load affected performance did not selectively reflect individual differences in distractor suppression or target enhancement 13 . Instead, individual differences in the effect of distractor load on the relative distribution of attention to target versus distractor locations predicted the effect of distractors on individual performance.…”
Section: Resultsmentioning
confidence: 89%
“…This strategy of using a slightly earlier time window for the P D component than the N2pc component is consistent with several previous studies (e.g., Sawaki & Luck, 2010; Weaver et al, 2017). Relative to the more common mean amplitude measures, positive and negative area measures are typically less impacted by latency differences between subjects (see Luck, 2014) and are therefore more appropriate for assessing correlations with behavioral measures (e.g., see Gaspar et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…The P D often appears exclusively in response to to-be-ignored salient items in the absence of an N2pc component (e.g., Gaspar, Christie, Prime, Jolicoeur, & McDonald, 2016; Gaspar & McDonald, 2014; Jannati, Gaspar, & McDonald, 2013; Sawaki & Luck, 2010, 2011). The P D also has a larger amplitude on fast-response trials than slow-response trials (e.g., Gaspar & McDonald, 2014; Jannati, Gaspar, & McDonald, 2013; McDonald, Green, Jannati, & Di Lollo, 2013), suggesting that suppression of a salient item allows faster detection of the target stimulus.…”
Section: The Signal Suppression Hypothesismentioning
confidence: 99%
“…With regard to attentional inhibition, visuospatial working memory (WM) may be important because of its role in an individual’s ability to filter relevant from irrelevant visual information. Research has demonstrated that WM capacity predicts activity in the visual cortex when suppressing distracting information and that individuals with lower WM capacity have difficulty inhibiting attention to task-irrelevant information (34), an effect exacerbated by dysphoria (35). Additionally, there is a well-established link between MDD and WM deficits (36), and evidence that WM training can improve dysphoric individuals’ ability to filter irrelevant information from visual attention (37).…”
Section: Introductionmentioning
confidence: 99%